2004
DOI: 10.1083/jcb.200310046
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the putative sterol-sensing domain of yeast Niemann Pick C–related protein reveals a primordial role in subcellular sphingolipid distribution

Abstract: Lipid movement between organelles is a critical component of eukaryotic membrane homeostasis. Niemann Pick type C (NP-C) disease is a fatal neurodegenerative disorder typified by lysosomal accumulation of cholesterol and sphingolipids. Expression of yeast NP-C–related gene 1 (NCR1), the orthologue of the human NP-C gene 1 (NPC1) defective in the disease, in Chinese hamster ovary NPC1 mutant cells suppressed lipid accumulation. Deletion of NCR1, encoding a transmembrane glycoprotein predominantly residing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
129
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(146 citation statements)
references
References 55 publications
15
129
0
Order By: Relevance
“…Given that the present data disrupted endocytic trafficking may only engage a small percentage of the total cholesterol pool. This is consistent with the yeast NPC model where altered localization of sphingolipids occurred without a large increase in ergosterol levels (61).…”
Section: Discussionsupporting
confidence: 77%
“…Given that the present data disrupted endocytic trafficking may only engage a small percentage of the total cholesterol pool. This is consistent with the yeast NPC model where altered localization of sphingolipids occurred without a large increase in ergosterol levels (61).…”
Section: Discussionsupporting
confidence: 77%
“…This contrasts with the itinerary for cholesterol in mammalian cells, in which lipoprotein-associated cholesterol is internalized by receptor-mediated endocytosis and is trafficked to late endosome/lysosomes. Third, deletion of Ncr1p in yeast indicates that this protein is not required for endocytic transport and sterol metabolism in yeast, because unlike in mammalian cells, such a deletion does not promote sterol accumulation in the vacuole (35,36). However, when Ncr1p is expressed in NPC1-null CHO cells, it is able to suppress the mutant phenotype, indicating that the yeast ortholog is competent with respect to sterol trafficking (35).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mutagenesis studies of the sterol-sensing domain of the NPC1 yeast ortholog, Ncr1p, have suggested a role for this region in cellular sphingolipid trafficking (35). In yeast, expression of the Y718D mutant, which corresponds to the mammalian SCAP D443N mutation, resulted in redistribution of PM-derived sphingolipids to the vacuole and other subcellular compartments, although no alterations in sterol metabolism were observed in this mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol removal from the endosome depends on the NPC1 protein, which contains a sterol-sensing domain. Like its plasma membrane counterpart NPC1L1 [37 ], it transports cholesterol (and possibly sphingolipids [38]) towards the cytosol by a mechanism that is unclear but may involve vesiculation. Cholesterol also modulates vesicular traffic at and after the early endosomes via annexin II [39,40].…”
Section: Selective Endocytosismentioning
confidence: 99%